“Fort. Ort. Wort.” Letteratura di ‘adozione’: sul caso di Tawada Yōko - Venezia, Simona (Itinerari, 2024)
The paper proposes the new category of ‘literature of adoption’, i.e. a literature that takes account of the unique situation of those contemporary writers who do not believe that the choice of the language with which they express their work is a necessarily passive or automatic process. Rather, they claim to consciously choose the language in which they convey their art. Starting from the innovative concept of Sprachmutter/Language Mother as formulated by the Japanese-German writer Tawada Yōko, the established certainties of the concept of Muttersprache/Mother Tongue understood as an incontrovertible foundation will be challenged in comparison with some of the most relevant philosophical investigations. The paper will discuss the perspective of the exophony, in the name of inhabiting the In-Between [Zwischenraum] among languages that define new directions of relationship with the world. Expressing oneself in one’s Muttersprache is, in fact, a choice generated by one’s belonging to a given nation and culture, while choosing a Sprachmutter is the result of an orientation and not a determination, an openness and not a closure.